Development of intermediate-scale structure in the nighttime equatorial ionosphere - Bhattacharyya, A. (My University, 2010)
Equatorial plasma bubbles (EPBs), a phenomenon observed in the nighttime equatorial ionosphere, are an important component of space weather. EPBs are associated with irregularities of the ionospheric plasma that span a large range of scale sizes of which the intermediate-scale size (similar to 400 m to a few kilometers) irregularities are capable of scattering incident radio waves of VHF and higher frequencies to produce a pattern of varying signal amplitude and phase, as the signal propagates to a ground receiver. Movement of the irregularities across the signal path causes the amplitude and phase of the signal recorded by a receiver to undergo temporal fluctuations or scintillations, which can adversely affect the operation of satellite-based communication and navigation systems. EPBs occur because of the growth of a generalized Rayleigh-Taylor instability on the bottom-side of the nighttime equatorial ionosphere, and nonlinear development of the instability depends on ambient ionospheric conditions. As the severity of signal degradation depends on the strength as well as the spectrum of the irregularities, it is of great interest to identify the ambient ionospheric conditions that determine the complexity of structures generated by the instability. This chapter presents the current status of our understanding of this problem based on observations and theoretical models, with an emphasis on scintillation-producing intermediate-scale irregularities in the postsunset equatorial ionosphere, as intense scintillations are indicative of an extreme phenomenon in the Earth's ionosphere.
Edited by:Sharma, AS (Sharma, AS) ; Bunde, A (Bunde, A) ; Dimri, VP (Dimri, VP) ; Baker, DN (Baker, DN): EXTREME EVENTS AND NATURAL HAZARDS: THE COMPLEXITY PERSPECTIVE, Book SeriesGeophysical Monograph Series, Volume196, Page279-292 DOI10.1029/2011GM001078, Published2012
Keywords: F-region irregularities; Rayleigh-Taylor instability; Receiver scintillation dataspread-F; Plasma bubble; Spectral characteristics; Numerical simulation; Schaotic behavior